HPV16E6-Dependent c-Fos Expression Contributes to AP-1 Complex Formation in SiHa Cells - Feixin Liang; Shinichiro Kina; Hiroyuki Takemoto; Akira Matayoshi; Thongsavanh Phonaphonh; Nao Sunagawa; Keiichi Arakaki; Akira Arasaki; Hai Kuang; Hajime Sunakawa (Mediators of Inflammation)
To date, the major role of HPV16E6 in cancer has been considered to be its ability to inhibit the p53 tumor-suppressor protein, thereby thwarting p53-mediated cytotoxic responses to cellular stress signals. Here, we show that HPV16E6-dependent c-fos oncogenic protein expression contributes to AP-1 complex formation under oxidative stress in SiHa cells (HPV16-positive squamous cell carcinoma of the cervix). In addition, we examined the role of HPV16E6 in TGF-α-induced c-fos expression and found that the c-fos protein expression induced by TGF-α is HPV16E6 dependent. Thus, our results provide the first evidence that HPV16E6 contributes to AP-1 complex formation after both ligand-dependent and independent EGFR activation, suggesting a new therapeutic approach to the treatment of HPV-associated tumors.